2013
DOI: 10.1093/annonc/mdt159
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen receptor co-activator AIB1 is a marker of tamoxifen benefit in postmenopausal breast cancer

Abstract: BackgroundThe oestrogen receptor (ER) co-activator amplified in breast cancer 1 (AIB1) has been suggested as a treatment predictive and prognostic marker in breast cancer. Studies have however not been unanimous.Patients and methodsAIB1 protein expression was analysed by immunohistochemistry on tissue micro-arrays with tumour samples from 910 postmenopausal women randomised to tamoxifen treatment or no adjuvant treatment. Associations between AIB1 expression, clinical outcome in the two arms and other clinicop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 24 publications
3
14
0
Order By: Relevance
“…The cumulating evidence, which argues against a strong contribution (40,41), is consistent with our data as we detected a downregulation of AIB1 in recurrent tamoxifen-resistant tumors.…”
Section: Discussionsupporting
confidence: 92%
“…The cumulating evidence, which argues against a strong contribution (40,41), is consistent with our data as we detected a downregulation of AIB1 in recurrent tamoxifen-resistant tumors.…”
Section: Discussionsupporting
confidence: 92%
“…Activator of thyroid and retinoid receptor (known as SRC‐3), located in a frequently amplified region, 20q12, is overexpressed in multiple cancers, such as breast, liver, gastric and prostate cancer 14,25‐27 . However, the detailed mechanisms and influence of ACTR on carcinoma treatment still require investigation.…”
Section: Discussionmentioning
confidence: 99%
“…AIB1 is a nuclear receptor co‐activator and works as a prognostic marker that promotes breast cancer growth and tamoxifen resistance . AIB1 amplification and over‐expression were found in aggressive breast cancers associated with high histological grade, poor prognosis and tamoxifen resistance . Our findings suggested that salinomycin was able to increase tamoxifen sensitivity by decreasing mRNA and protein expression of AIB1 in endocrine‐resistant breast cancer cells.…”
Section: Discussionmentioning
confidence: 57%